Delayed percentage attenuation ratio (DPAR) on multiphase CT as a quantitative predictor of early response in hepatocellular carcinoma - Yana Supriatna; Rifki Bachtiar; Muhammad Y. Makkaraeng; Arif Budiman (Narra J, 2026)
Hepatocellular carcinoma (HCC) remains a major cause of cancer-related mortality, and transarterial chemoembolization (TACE) is the standard therapy for intermediate-stage disease. However, response to TACE is variable, and reliable quantitative imaging biomarkers are needed to support early treatment decision-making. This study aimed to evaluate the predictive value of the delayed percentage attenuation ratio (DPAR) measured from pre-TACE multiphasic computed tomography (CT) in forecasting early therapeutic response. A retrospective cross-sectional study was conducted involving patients with a definitive diagnosis of HCC who underwent their first TACE session and had complete multiphasic CT imaging before and after treatment. Quantitative washout parameters, delayed percentage attenuation ratio (DPAR), absolute washout (WOAbs), and relative washout (WORel) were measured using standardized region of interest (ROI) placement by three radiologists. Treatment response was assessed four to six weeks post-TACE based on modified Response Evaluation Criteria in Solid Tumors (mRECIST) criteria and classified into responders and non-responders. Diagnostic performance was evaluated using receiver operating characteristic (ROC) analysis, and interobserver reliability was assessed using intraclass correlation coefficient (ICC) and Cohen’s κ. A total of 49 HCC patients were included and analyzed. Responders demonstrated significantly higher DPAR values compared with non-responders (median 134.5 vs 113.0; p<0.001). DPAR showed the strongest discriminative performance with an area under the curve (AUC) of 0.898, outperforming WOAbs (AUC 0.689) and WORel (AUC 0.704). The optimal DPAR threshold of ≥120.5 provided 84.4% sensitivity and 88.2% specificity to predict early post-TACE treatment response. Interobserver reliability was excellent for all washout parameters (ICC 0.98–0.99), and agreement for mRECIST classification was also excellent (κ=0.867). In conclusion, pre-TACE DPAR is a robust and reproducible quantitative imaging biomarker that accurately predicts early response to TACE in HCC. A threshold value of ≥120.5 may assist in treatment planning and patient selection in routine clinical practice.